The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1017/s1068280500004627
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Parcel Structure on the Efficiency of Finnish Dairy Farms

Abstract: In Finland, expanding dairy farms often face the problem of additional fields being geographically distant and only available as small parcels. We develop a stochastic production frontier model to estimate the technical efficiency of Finnish dairy farms and simulate the effect of parcel distance and parcel size on the efficiency of an average farm for 2000 through 2009. The overall development of technical efficiency is positive during the study period but increases in distance and decreases in parcel size bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 64 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Del Corral et al (2011) find that larger farm sizes lead to increased technical inefficiency, but interaction effects are not considered. Niskanen and Heikkilä (2015) note that increasing parcel size reduces technical inefficiency while parcel distance increases technical inefficiency. 19 Del Corral et al (2011) and Carroll et al (2007) report herd size elasticities of 0.68 and 0.67 respectively.…”
Section: Input Elasticitiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Del Corral et al (2011) find that larger farm sizes lead to increased technical inefficiency, but interaction effects are not considered. Niskanen and Heikkilä (2015) note that increasing parcel size reduces technical inefficiency while parcel distance increases technical inefficiency. 19 Del Corral et al (2011) and Carroll et al (2007) report herd size elasticities of 0.68 and 0.67 respectively.…”
Section: Input Elasticitiesmentioning
confidence: 98%
“…We use a stochastic production frontier (SPF) model (Aigner et al, 1977), to estimate technical inefficiency. This approach was also used by Del Corral et al (2011), Orea et al (2015, Niskanen and Heikkilä (2015) and Mehmood et al (2018). Specifically,…”
Section: Empirical Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, large dairy farms, which have recently invested in larger cattle houses, have high capital costs and produce higher milk yields with a higher turnover per animal. This is to achieve high gross margins, cover capital costs and thus achieve a shorter payback time of farm debts [16]. Low milk yields are considered clearly uneconomic (ibid).…”
Section: Introductionmentioning
confidence: 99%
“…Areal et al (2012) found that spatial dependence among dairy farms in England and Wales is important in explaining variation in technical efficiency. Niskanen and Heikkilä (2015) focused on the effect of farmland parcel fragmentation on technical efficiency of Finnish dairy farms.…”
Section: Introductionmentioning
confidence: 99%